Abnormalities of early folliculogenesis and serum anti-Müllerian hormone in chinese patients with polycystic ovary syndrome - Juan Du; Xiangyan Ruan; Fengyu Jin; Yanglu Li; Jiaojiao Cheng; Muqing Gu; Alfred Otto Mueck (BMC, 2021)
Abstract Purpose To investigate abnormalities of early folliculogenesis and Anti-Müllerian hormone (AMH) concentrations in polycystic ovary syndrome (PCOS) patients, and to analyze the association between AMH and early-stage follicle densities (FD). Methods A total of 175 patients underwent ovarian tissue cryopreservation in the first official cryobank in China, of which 16 patients aged 30-40 years old were diagnosed with endometrial cancer (all without initial chemo/radiotherapy), including 5 patients with concurrent PCOS and the other 11 patients without. We obtained standard cortical biopsies to measure FD using calcein staining. Blood samples were collected before cryopreservation to evaluate AMH concentrations. Results PCOS showed nearly three times the primordial and primary FD than NPCOS (P = 0.027), as well as more secondary preantral follicles (P = 0.002). A significantly higher proportion of secondary preantral follicles and a lower proportion of primordial and primary follicles were observed in PCOS (P = 0.01). Furthermore, the AMH concentration in PCOS was four times higher than that in NPCOS (P = 0.003), which is significantly correlated with primordial and primary follicle densities (r = 0.855, P < 0.001) and secondary preantral follicle densities (r = 0.732, P = 0.007). Conclusions We found significant disorders of early folliculogenesis in PCOS, which showed close correlation with increased AMH concentrations. To our knowledge, abnormalities of early-stage follicles have been shown for the first time in ovarian tissue of Chinese PCOS women. We suppose that the elevated AMH level is associated with abnormalities of early folliculogenesis within the complex PCOS pathogenesis, which may explain why AMH has the potential to be used as a biomarker for the diagnosis of PCOS. Our findings provide more implications for understanding the mechanism of PCOS, and new directions for further studies.